Burnout in health personnel and its prevention: A systematic review - Rivera Salazar, Geny Margoth (2024)
Burnout syndrome causes both mental and physical exhaustion and is especially prevalent among health professionals. The objective of this research is to identify effective Burnout syndrome prevention strategies for health professionals.  For this purpose, a systematic review of the literature was carried out, where the Kitchenham review methodology, the PICO structure to formulate the research question and the PRISMA guidelines were used. A total of 1293 articles from selected databases were analyzed, which were finally reduced to 13 relevant articles. The findings highlighted the effectiveness of organizational strategies in medical settings, but their direct impact on Burnout syndrome is inconclusive due to its multifaceted nature. Although personal interventions showed success in mitigating negative emotions, concerns were raised regarding the sustainability of their effects. Notable limitations include the lack of standardized outcome measures across studies.